Macro Economic Determinants of Economic Growth In South Africa: A Cointegration Evidence (Journal of Academic Finance, 2025)
Purpose: To investigate the determinants of economic growth in South Africa amidst ongoing macroeconomic challenges.Method: Utilized yearly time series data. Assessed data stationarity using the Phillips-Perron and Augmented Dickey-Fuller tests. Employed an Autoregressive Distributed Lag (ARDL) model to analyze short- and long-run relationships. Applied Granger causality to explore causal relationships among the variables.Results: In the long run, financial development, capital stock, and employment are significant determinants of economic growth. In the short run, all variables examined were significant.Originality/Relevance: The study addresses critical macroeconomic challenges in South Africa, providing insights that can inform policies aimed at stimulating economic growth through employment, investment in capital, and financial development.
Keywords: : South Africa, economic growth, capital stock, financial development, employment, inflation, Autoregressive Distributed Lag (ARDL).